2020
DOI: 10.1103/physreve.101.042135
|View full text |Cite
|
Sign up to set email alerts
|

Molecular fields and statistical field theory of fluids: Application to interface phenomena

Abstract: Using the integral transformation, the field-theoretical Hamiltonian of the statistical field theory of fluids is obtained, along with the microscopic expressions for the coefficients of the Hamiltonian. Applying this approach to the liquid-vapor interface, we derive an explicit analytical expression for the surface tension in terms of temperature, density and parameters of inter-molecular potential. We also demonstrate that a clear physical interpretation may be given to the formal statistical field arising i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 45 publications
4
30
0
Order By: Relevance
“…Both modifications are relevant to describe the charge-charge correlations between charged particles in the one component plasma (OCP) at strong coupling, concentrated electrolytes, and room temperature ionic liquids. It has also been found that these two modifications explain the deviation from the PB solution for counterion distribution over a wide range of from the intermediate to strong coupling [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: A Variety Of Previous Self-consistent Equationsmentioning
confidence: 94%
See 4 more Smart Citations
“…Both modifications are relevant to describe the charge-charge correlations between charged particles in the one component plasma (OCP) at strong coupling, concentrated electrolytes, and room temperature ionic liquids. It has also been found that these two modifications explain the deviation from the PB solution for counterion distribution over a wide range of from the intermediate to strong coupling [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: A Variety Of Previous Self-consistent Equationsmentioning
confidence: 94%
“…( 9). Modified PB equations for the Coulomb potential Ψ(r) [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].-Lastly, we mention two types of modified PB equations (see Appendix A for the details). Both modifications are relevant to describe the charge-charge correlations between charged particles in the one component plasma (OCP) at strong coupling, concentrated electrolytes, and room temperature ionic liquids.…”
Section: A Variety Of Previous Self-consistent Equationsmentioning
confidence: 99%
See 3 more Smart Citations